Economic geography. - Hodder, B. W.; Lee, Roger (London: Methuen & Co Ltd., 1974)
This book introduces the reader to the many lines of thought in the literature on economic geography and ties these various aspects together within the concept of the economy. The book focuses on the dynamic and integrated nature of economies at different scales and levels of development.
aia 06/09/18
Keywords: Economic geography; Economic growth; Economic conditions; .